Understanding Passenger Satisfaction: Topic Modeling of Online Reviews - Saidah, Faridatus; Lestari, Yuliani Dwi (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
This study examined customer satisfaction with three airlines— Garuda Indonesia, Batik Air, and Citilink—by analyzing Skytrax customer reviews. Topic modeling based on latent Dirichlet allocation (LDA) was used to categorize 1174 customer reviews from 2024 as having either positive or negative sentiment. The statistical analysis revealed that Garuda Indonesia received the most recommendations, followed by Citilink and Batik Air. Positive review themes included good service and friendly staff, whereas negative sentiment was frequently attributed to delays and poor seat comfort. By identifying these key satisfaction drivers and pain points, this study offers actionable insights for airline service improvement and customer retention strategies. These findings contribute to the growing application of text mining in consumer behavior research and provide practical guidance for airline managers aiming to optimize competitiveness in the aviation industry.